2002
DOI: 10.1128/jvi.76.16.8200-8207.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Architecture of Adenovirus DNA Polymerase and Location of the Protein Primer

Abstract: Adenovirus (Ad) DNA polymerase (pol) belongs to the distinct subclass of the pol␣ family of DNA pols that employs the precursor terminal protein (pTP) as primer. Ad pol forms a stable heterodimer with this primer, and together, they bind specifically to the core origin in order to start replication. After initiation of Ad replication, the resulting pTP-trinucleotide intermediate jumps back and pTP starts to dissociate. Compared to free Ad pol, the pTP-pol complex shows reduced polymerase and exonuclease activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…5). To examine the specificity of the stimulation of Pol binding by DBP on the ssDNA template T50, we used an exonuclease-deficient Pol mutant (Pol exo mutant, D422A) because wild-type Pol is known to degrade ssDNA in the absence of deoxynucleoside triphosphates (5). Stimulation of Pol binding to TD50 with the Pol exo mutant was similar to wildtype Pol binding (compare Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5). To examine the specificity of the stimulation of Pol binding by DBP on the ssDNA template T50, we used an exonuclease-deficient Pol mutant (Pol exo mutant, D422A) because wild-type Pol is known to degrade ssDNA in the absence of deoxynucleoside triphosphates (5). Stimulation of Pol binding to TD50 with the Pol exo mutant was similar to wildtype Pol binding (compare Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The adenovirus proteins ⌬N-DBP, PPP-DBP, Pol, Pol exo mutant (D422A), and pTP were expressed in baculovirus-infected Sf9 cells and purified to near homogeneity, as verified by silver staining as described previously (5,6,9,34). Phage T4 gp32 and T4 Pol were purchased from Amersham Pharmacia Biotech.…”
Section: Methodsmentioning
confidence: 99%
“…The crystal structure of AdV Pol has not been determined, but sequence comparisons with polymerases of known structure as well as biochemical and mutagenesis studies have revealed AdV Pol's general domain organization ( Fig. 2) (Joung et al 1991;Joung and Engler 1992;Knopf 1998;Liu et al 2000;Brenkman et al 2001Brenkman et al , 2002Liu et al 2003). Besides consisting of the common polymerase subdomains palm, fingers, and thumb, which are associated with 5 0 -3 0 polymerase activity, AdV Pol carries a 3 0 -5 0 exonuclease domain that is necessary for its intrinsic proofreading ability (King et al 1997;Brenkman et al 2002;Liu et al 2003).…”
Section: The Adv Dna Polymerasementioning
confidence: 99%
“…Inverted terminal regions (ITRs) are known to contain replication origins where the DNA polymerase and TP bind together and initiate DNA replication (47,48) and are also known to form the "panhandle structure" of the intramolecular double helix for replication (49). DBP binds the viral DNA and enhances the replication initiation by DNA polymerase and pTP at the ITRs (47,50). The multiple physical interactions of ITRs with DNA polymerase, pTP, DBP, and themselves for replication are similar to the protein interactions mentioned above.…”
Section: Discussionmentioning
confidence: 79%